Ecological Restoration of Coastal Wetlands Under Global Climate Change: A Case Study of Tianjin - Jin, Shangyu (Transactions on Engineering and Technology Research, 2024)
The coastal zones of Tianjin, China, harbored vital ecosystems, including salt marshes and wetlands, which provided essential ecological services such as water purification, carbon sequestration, flood mitigation, and biodiversity conservation. However, increasing global climate change impacts, along with intensive human activities like land reclamation and industrial development, led to significant degradation of these ecosystems. This paper presented a detailed analysis of the "Retreat Ponds, Restore Wetlands" project in Qilihai Wetland, focusing on ecological interventions such as channel dredging, vegetation recovery, and habitat improvement. These efforts aimed to rehabilitate the degraded wetland, and their effectiveness was assessed in terms of ecological recovery, water quality improvement, and biodiversity enhancement, particularly in the return of migratory bird species and the regeneration of key plant species like reeds. Additionally, the study explored the resilience of the restored ecosystem in the face of rising sea levels, increasing soil salinity, and changes in hydrological cycles. The findings emphasized the limitations of traditional restoration approaches and highlighted the need for adaptive, innovative methods that integrate modern technologies, such as ecological monitoring and big data analysis, to ensure long-term ecosystem sustainability. The research also underscored the importance of interdisciplinary collaboration in restoration efforts, combining ecological science, climate adaptation strategies, policy reform, and public engagement to enhance the resilience of coastal ecosystems under future climate uncertainties.